Investigation of Cybersecurity Vulnerabilities and Mitigation Strategies in Nigeria's Oil and Gas Industry - Ebelogu, Christopher Ubaka; Prasad, Rajesh; Bisallah, Hashim Ibrahim; Hammawa, Baba Mohammed; Musa, Israel (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
As Africa's largest oil producer, Nigeria heavily relies on its Oil & Gas (O&G) sector, which significantly contributes to the nation's GDP, export profits, and government revenue. However, this sector faces substantial challenges due to its susceptibility to cyberattacks, which exploit the vast amounts of sensitive data generated across its operations. These threats have become more prominent with the integration of digital technologies, increasing the sector's vulnerability. Despite efforts like the Nigerian Data Protection Regulation, cyber incidents like ransomware and Advanced Persistent Threats (APTs) continue targeting critical infrastructure, leading to severe financial, operational, and environmental impacts. The rising frequency of such attacks highlights the urgent need for enhanced cybersecurity measures within Nigeria's O&G industry. This study aims to investigate the cybersecurity landscape in the sector, focusing on identifying prevalent cyber threats and assessing the effectiveness of current control measures. Through systematically analyzing existing research and data, the study seeks to provide insights into the evolution of cyber threats and propose strategies for strengthening the sector's cybersecurity posture.